An Experimental Study on Bond Behavior of Rebar and High-Performance Fiber Reinforced Cementitious Composite (HPFRCC) at High Temperatures - Salim Karimpour; Rahmat Madandous; Malek Mohammad Ranjbar; Habib Akbarzadeh Bengar (Journal of Rehabilitation in Civil Engineering)
In this work, it was attempted to explore the bond behavior of rebars in high-performance fiber-reinforced cementitious composite (HPFRCC) consisting of hybrid fibers with 1 and 2% by weight of binder for steel and 0.1, 0.2, 0.3, and 0.4% by weight of binder for polypropylene (PP) and polyvinyl alcohol (PVA) fibers along with the compressive and tensile strengths after exposure to high temperature. From 19 mix designs, four superior ones which experienced lower reduction in compressive strength at 400 and 600 oC was selected in order to investigate the bond behavior of rebar in HPFRCC specimens using direct pullout and RILEM beam tests. The experimental results revealed that the HPFRCC specimens with 1% steel fiber combined with 0.2% PP fiber and 0.3% PVA fiber, separately, had the minimum compressive strength loss at 400 and 600 °C. For the HPFRCC with 2% steel fiber, the higher compressive strength at the given temperatures was observed for those with 0.3% PP and 0.2% PVA fiber, separately. The specimens with higher compressive strength at the given temperatures were those that had 2% steel fibers, 0.3% PP, and 0.2% PVA fibers. The specimen with 1% steel fibers and 0.3% polypropylene fibers had a greater tensile strength with a value of 14.2 MPa compared to other specimens. Furthermore, the bond capacity of rebar in HPFRCC continues to decline with temperature rise up to 600 °C to the point where this reduction for the chosen specimens is approximately 62% of the bond strength of the specimens at the room temperature (i.e., 23 °C). The maximum pull-out force has a significant relationship with the type and proportion of fibers, as demonstrated by the RILEM beam's results. Compared to specimens containing PP fibers, those with PVA fibers at high temperatures were able to tolerate higher bond strength.